KAJIAN EKOLOGI PASAK BUMI (Eurycoma longifolia Jack) DAN PEMANFAATAN OLEH MASYARAKAT DI SEKITAR HUTAN LARANGAN ADAT RUMBIO, KABUPATEN KAMPAR PROVINSI RIAU - Hasibuan, Sapruddin; Suhesti, Eni; Insusanty, Enny (Wahana Forestra: Jurnal Kehutanan, 2016)
Pasak bumi is one kind of medicinal plants commonly consumed by people and grow in Prohibition of Indigenous Forests Rumbio. Information on the ecological conditions Pasak bumi in Prohibition of Indigenous Forests Rumbio is important known as an indicator of the presence of Pasak bumi, and their population in the forest. The purpose of this study to analyze the ecological conditions Pasak bumi in Prohibition of Indigenous Forests Rumbio , and know how to use Pasak bumu conducted by people around the Prohibition of Indigenous Forests R umbio. The method used in this study was a survey method, the implementation of the research started from the observation, creating a plot, measurement, and data acquisition. The average temperature in the research location 28,09 0 C, average air humidity 85.38%, and the average light intensity of 582.20 lux, type of soil is Red Yellow Podzolic, w ith a pH of 5.5-6.4. Pasak bumi found in site which it is flat and slopes for 15%, with an altitude of 600-750 m above sea level. Pasak bumi grown on sloping ground that is not waterlogged. Communities around the Prohibition of Indigenous Forests Rumbio utilize Pasak bumi from the leaves, stems, bark and roots. The perceived benefits of the Pasak bumi by society is to improve blood circulation, eliminate fatigue, malaria drugs, smooth urination, mouth sores, itching disease medicine, a tonic after childbirth and fever.